Pelatihan Pijat Bayi Sebagai Upaya Bounding Attachment di Desa Bongan, Kabupaten Tabanan - Gampur, Imelda Rismayani; WINANGSIH, RINI; Sulastina, Elisabet (STIKES Advaita Medika Tabanan, 2024)
Children are the future of the country, it is important to ensure they grow and develop to their full potential. However, in reality, there are obstacles that impact children's growth and development. Other problems are a lack of awareness of the benefits of baby massage therapy in encouraging children's growth and development, the inability of volunteers or health cadres to provide safe and effective baby massage therapy, as well as financial limitations that make baby massage therapy unaffordable for the poor. The aim of doing baby massage is as an effort to bond attachment. The preparation stage is carried out during the assessment and approach. The implementation stage is carried out by providing information about baby massage and. The evaluation stage is carried out by assessing the mother's knowledge and skills in carrying out baby massage. The result: the preparation stage by visiting the Bongan village head to find out the profile of the village population and prepare the main and supporting facilities. In the implementation stage of delivering baby massage training material, cadre participants who previously did not have sufficient knowledge about baby massage, after the training, their knowledge and skills increased. In the evaluation stage, mothers are given an in-depth understanding of the benefits of baby massage therapy, appropriate baby massage techniques, as well as medical knowledge related to their child's growth and development. They will receive direct direction and assistance from a competent trainer. In conclusion: Community Service activities related to baby massage training as a Bounding Attachment effort were carried out in Bongan Village, Tabanan Regency on Thursday, July 4 2024, which was attended by 28 people. Keywords : Training, baby massage, bounding attachment